Efficient partnership formation in networks - Francis Bloch; Bhaskar Dutta; Mihai Manea (Theoretical Economics, 2019)
We analyze the formation of partnerships in social networks. Players need favors at random times and ask their neighbors in the network to form exclusive long-term partnerships that guarantee reciprocal favor exchange. Refusing to provide a favor results in the automatic removal of the underlying link. Players agree to provide the first favor in a partnership only if they otherwise face the risk of eventual isolation. In equilibrium, players essential for realizing every maximum matching can avoid this risk and enjoy higher payoffs than inessential players. Although the search for partners is decentralized and reflects local partnership opportunities, the strength of essential players drives efficient partnership formation in every network. Equilibrium behavior is determined by the classification of nodes in the Gallai-Edmonds decomposition of the underlying network.
Keywords: C78; D85; 330; Networks; efficiency; decentralized markets; partnerships; favor exchange; maximum matchings; Gallai-Edmonds decomposition; under-demanded